Characteristics of growth and location of rural population of Surkhandarya region (Zien Journal of Social Sciences and Humanities, 2022)
This article highlights information about the population, the location of settlements, the housing of the population, the structure of dwellings, as well as the economic, social and geographical changes that influenced the development of the region, it should be noted that the study of population growth, the location of settlements has great economic and social importance. The location of industrial facilities (plants, factories) in rural settlements has a positive effect on the employment of the population, which is the priority tasks today. The improvement of rural settlements today is directly related to the development of agro-economic complexes, that is, a market economy in rural areas. Experience shows that the development of agro-industrial complexes in the Surkhandarya region, specialized in cotton growing, growing fruits and viticulture, gives very good results, thanks to natural climatic conditions, that is a lot of sunny days (solar radiation) per year